IMPORT OF COMPONENTS FOR FEW RECOGNIZED CELL PHONES - Gustavo Ruiz Burgos, Héctor; Laureano Rojas, Tito; Alberto Arias Davalos, Zhris (Revista Gênero e Interdisciplinaridade, 2023)
Currently there is a growth in the demand for cell phones of unrecognized brands. These devices may present technical failures or of the physical components themselves, which in most cases requires the replacement of the damaged part. The main difficulty is finding the necessary spare parts for the repair since they are imported components and in most cases it leads to running out of the mobile device for several days or weeks. For this research, the survey technique was applied, addressed to 8 companies that import spare parts for cell phones who are located in the Jebai Center Gallery in Ciudad del Este, through the elaboration of a questionnaire with closed questions, with the objective of knowing the difficulties that prevent the importation of spare parts for little-recognized cell phone brands, the approach used was quantitative and the level of research was descriptive. Thanks to the results of the data collection instrument, it was possible to identify that the main difficulties that prevent the importation of spare parts for little-known cell phone brands are the high import taxes.